ANALISIS DAMPAK STOCK SPLIT TERHADAP VOLUME PERDAGANGAN SAHAM DAN RETURN SAHAM DI BURSA EFEK INDONESIA - Yunitasari, Shelli; Mursalin, Supardi; Stiawan, Evan (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study was to determine the impact of stock splits on stock trading volume and stock returns. This type of research is descriptive quantitative. The population in this study are all companies listed on the Indonesia Stock Exchange and included in the Indonesian Sharia Stock Index (ISSI). The sample selection technique was purposive sampling and obtained 19 companies that did Stock split during the 2021-2023 period. The analysis method of this research uses simple linear regression analysis using SPSS 27. The results of this study indicate that: (1) Stock split has a negative impact on stock trading volume. This can be seen in the results of the value (tcount) -0,430 > 2,120 (ttable) and sig value 0,673 < 0,05. (2) Stock split has a positive impact on stock returns. This can be seen in the results of the value (tcount) 2,567 > 2,120 (ttable) and sig value 0,041 < 0,05.